Social Networks and WEB ontologys as perfect couple for knowledge management tool/system - Idrizi, Florim; Ilazi, Uran; Asani, Florin (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The social networks have become a main tool of the XXI century for personal presentation and promotion, connectivity with others, belonging to same ideology, area of expertise or culture. Beside all the exploitations made to the social networks, lets pose the question: Are social networks and social network medias pushed to their limits, are they manageable and do they give as maximal possibilities in using, managing and having all the knowledge stuffed in there and using it to benefit of our research? Combining the social networks with semantic web can enhance the process of education and research.